Laporan Kasus Kekeruhan Kornea Kongenital: Tantangan Operasi Keratoplasti pada Anak-Anak : Laporan Kasus - Yulia, Dian Estu; Pradiptama, Yura; Tan, Sabrina (Cermin Dunia Kedokteran, 2025)
Introduction: Congenital corneal opacity (CCO) is a group of anterior segment dysgenesis of the eye manifested by corneal transparency loss at birth or during the first 4 weeks of life. CCO is one of the most prominent disease entities in anterior segment dysgenesis. CCO resulted from disruptions in mesodermal development, particularly affecting the anterior segment of the eye. Case:A 2-week-old boy with bilateral CCO. One week post-keratoplasty surgery, the parents reported no complaints but had difficulty administering eye drops. Physical examination showed a clearer corneal graft. One month later, a cloudy graft and broken sutures were noted, indicating graft rejection. The family was educated on the importance of consistent medication for any future graft surgery. Discussion: The surgical option for CCO is corneal graft or keratoplasty. Keratoplasty is a corneal transplant where a clear donor graft replaces the central opaque cornea. Conclusion: A comprehensive workup is essential for diagnosing CCO. Keratoplasty can restore corneal clarity and vision, but pediatric cases require careful patient education and comprehensive follow-up.